Assessing Regional Risks From Pandemic Influenza: A Scenario Analysis. (1st August 2015) - Verikios, George; Sullivan, Maura; Stojanovski, Pane; Giesecke, James; Woo, Gordon
Abstract: We analyse the economic risks from two influenza pandemics that represent extremes along the virulence‐infectiousness continuum of possible pandemics: a high virulence–low infectiousness event and a low virulence–high infectiousness event. Our analysis involves linking an epidemiological model and a quarterly computable general equilibrium model. We find that global economic activity is more strongly affected by a pandemic with high infection rates rather than high virulence rates, all else being equal. Regions with a higher degree of economic integration with the world economy face greater risks of negative effects than less integrated regions.